The (Semi) State’s Fragility: Hamas, Clannism, and Legitimacy - Abdalhadi Alijla (MDPI AG, 2021)
This article shall ask how Hamas, as a non-state actor, negotiated legitimacy with the clans in a fragmented and factionalized tribal society in the Gaza Strip from 2007–2011. An important factor that shapes the extent of power of rebels and non-state actors in limited statehood areas (LSA) pertains to the negotiation of power these rebels develop with clans in certain areas or times. Rebel governance is a complex and multidimensional concept shaped by the pre-existing particularity of the rebel, its identity, level of factionalism, the former structure of administration, and the extant political institutions. This paper will discuss Hamas as a contemporary case of rebel governance in war and post-war times, which has resulted in a special case of fragile governance. Based on ethnographic research on Hamas and insights from political theories of identity and governance, this paper suggest that tribal factionalism led to violence and played a major role in shaping the governance structure and mechanisms through political affiliation, informal judicial mechanisms, and as a part of the social network which resists government authority. This paper shall propose that Hamas used two paths of negotiations with clans: a coercive power (violent), and by mobilizing individuals of these clans and families as part of the informal judicial system (U’rf). This research aims to contribute to the understanding of rebel governance in general, and Hamas in particular, showing how struggle over legitimacy is shaped and negotiated, and why Hamas could be considered a special case in the study of rebel governance.